The ape who guards the balance - Peters, Elizabeth, 1927-2013 (Peters, Elizabeth, 1927-2013. Amelia Peabody series., 2010)
Amelia Peabody, her husband Radcliffe, their clever son Ramses, Ramses' friend David, and their ward Nefret Forth wreak havoc in Edwardian Egypt when a rare papyrus ends up in the possession of the young people and disaster follows in the form of angry ancient gods, a criminal mastermind, and a brutal killer.